Plan de negocio para la implementación de un camión de comida rápida saludable en la ciudad de Quito, Pichincha - Ecuador - Peñafiel Conde, Saskia Estefanía (2016)
The following business plan proposes the creation of Groovy Food Truck, a mobile restaurant dedicated to commercialize healthy fast food in Quito, the same which drive along the north of the city. The first chapter details the culinary industry history, as well as the history of food trucks, the culinary trends, and how food affects our health. In the second chapter detailed the legal permissions that the company needs to start their operation, also the description of the company, the mission, vision and goals in the short, medium, and long term; more than this SWOT analysis and competitive advantage analysis are realized, taking into consideration the direct and indirect competition existing. In the third chapter the market research are shown that obtained through surveys and it were made an analysis of each of the questions of the same. With the help of the third chapter results marketing strategies can be created that Groovy Food Truck will use for the fourth chapter, in which consists the 8P of the marketing mix. In the fifth chapter we have the presentation of the truck ruts throughout the city, as well as the architectural planes and the operating cycles which will be carried out. In the sixth chapter financial plan are made, the same that presents clear and credible estimates and assumptions of the financial results of the company. Finally, conclusions and recommendations that were collected throughout the development of the plan are presented.